EFFECT OF BLACK CUMIN OIL ADMINISTRATION ON CORTISOL LEVEL AND LIVER HISTOPATHOLOGY OF HEAT STRESSED BROILER CHICKENS - Hasan, Denny Irmawati; Sugito, Sugito; Sabri, Mustafa; Hambal, Muhammad; Balqis, Ummu (Jurnal Kedokteran Hewan, 2019)
The aim of this study was to observe cortisol levels and liver histopathology of broiler chicken that were treated with black cumin oil (BCO) under heat stress. A total of 15 broiler chickens were used in this study and divided into 5 groups, K- (without treatment), K+ (given heat stress), P1 (given heat stress and 0.56mL BCO/400kg body weight, P2 (given heat stress and 1.11 mL BCO/400 g body weight), and P3 (given heat stress and 2.22 mL BCO/400 g body weight). Heat stress was given for 5 hours with temperature range of 34-35 C for 7 days. Cortisol was measured using the cortisol enzyme-linked immunosorbent assay (ELISA) kit. Liver histopathology was stained with hematoxylin eosin and observed with electron microscope. The data were analyzed using one way analysis of variance (ANOVA). This study found that application of heat stress to broiler chickens increased cortisol levels and induced histopathological changes in the liver. The BCO administration reduced cortisol level significantly (P0.05) in heat-stressed broilers. BCO administration also significantly reduced (P0.05) the degenerative changes in liver histopathology such as fat degeneration, hemorrhage and necrosis in broiler chickens under heat stress, but did not significantly influence the inflammatory cells infiltration. As conclusion, BCO administration to broiler chickens under heat stress can reduce cortisol levels and minimize histopathological changes in the liver.